Marine omega-3 polyunsaturated fatty acid intake and survival after colorectal cancer diagnosis - Song, Mingyang (Gut, 2016)
OBJECTIVE: Experimental evidence supports an antineoplastic activity of marine omega-3 polyunsaturated fatty acids (ω-3 PUFAs; including eicosapentaenoic acid, docosahexaenoic acid, and docosapentaenoic acid). However, the influence of ω-3 PUFAs on colorectal cancer (CRC) survival is unknown. DESIGN: Within the Nurses’ Health Study and Health Professionals Follow-up Study, we prospectively studied CRC-specific and overall mortality in a cohort of 1,659 CRC patients according to intake of marine ω-3 PUFAs and its change after diagnosis. RESULTS: Higher intake of marine ω-3 PUFAs after CRC diagnosis was associated with lower risk of CRC-specific mortality (P for trend=0.03). Compared with patients who consumed less than 0.10 g/day of marine ω-3 PUFAs, those consuming at least 0.30 g/day had an adjusted hazard ratio for CRC-specific mortality of 0.59 (95% confidence interval [CI], 0.35 to 1.01). Patients who increased their marine ω-3 PUFA intake by at least 0.15 g/day after diagnosis had a hazard ratio of 0.30 (95% CI, 0.14 to 0.64, P for trend<0.001) for CRC deaths, compared with those who did not change or changed their intake by less than 0.02 g/day. No association was found between post-diagnostic marine ω-3 PUFA intake and all-cause mortality (P for trend=0.47). CONCLUSION: High marine ω-3 PUFA intake after CRC diagnosis is associated with lower risk of CRC-specific mortality. Increasing consumption of marine ω-3 PUFAs after diagnosis may confer additional benefits to patients with CRC.